Ginsenoside Rg2 Attenuated Trastuzumab-Induced Cardiotoxicity in Rats. (12th January 2022) - Liu, Guang; Zhang, Jinli; Sun, Fangyi; Ma, Jingtao; Qi, Xiaoyong
Abstract : Aim . Trastuzumab (TZM) is a monoclonal antibody drug for HER2-positive breast cancer by targeting epidermal growth factor 2, but it has significant cardiotoxicity. Ginsenoside Rg2 has shown a variety of biological activities. This study was aimed at investigating whether Rg2 attenuates TZM-induced cardiotoxicity. Methods . A model of TZM-induced cardiotoxicity was established in Wistar rats, and the rats were pretreated with Rg2. After echocardiography analysis, the rats were killed and the hearts were dissected for RNAseq analysis. Primary human cardiomyocytes (HCMs) were treated with TZM with or without pretreatment with Rg2 and then subjected to a colony formation assay, flow cytometry analysis, and Western blot analysis for the detection of caspase-3, caspase-9, and BAX. Results . TZM induced LV dysfunction in rats, but Rg2 could attenuate TZM-induced LV dysfunction. The mRNA levels of caspase-3, caspase-9, and BAX were significantly higher in TZM-treated rats. The colony formation ability of HCMs was significantly lower in TZM-treated cells but was recovered after pretreatment with Rg2. The apoptosis rate of HCMs was significantly higher in TZM-treated cells but was significantly lower after pretreatment with Rg2. Moreover, protein levels of caspase-3, caspase-9, and BAX were significantly higher in TZM-treated cells but were significantly lower after pretreatment with Rg2. Conclusion . Ginsenoside Rg2 inhibited TZM-induced cardiotoxicity, and the mechanism may be related to the downregulation of the expression of proapoptotic proteins caspase-3, caspase-9, and BAX and the inhibition of TZM-induced apoptosis in cardiomyocytes. Ginsenoside Rg2 has a potential to be applied in patients with breast cancer to prevent TZM-induced cardiotoxicity.